2021
DOI: 10.4103/jpbs.jpbs_745_21
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function Assessment in Saudi Males with Metabolic Syndrome

Abstract: Background: Metabolic Syndrome (MetS) is a multifactor condition associated with cardiovascular risk. Thyroid hormones regulate MetS components via controlling energy homeostasis, lipids, and glucose metabolism. The risk ratio for MetS and related disorders changes between males and females. Aim and Objectives: Study aim to access thyroid functions in Saudi population with metabolic syndrome. Materials and Methods: The current study sought to evaluate the impact of thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…The mean insulin and HOMA-IR index in our patients with metabolic syndrome were 20.8±4.3 mU/mL and 5.8±1.3, respectively. Almost similar levels of mean insulin and HOMA-IR index were reported by Aldhafiri et al in patients with metabolic syndrome [16]. Compared to the findings of the current study, almost similar levels of FBS, serum TG, and HDL were reported by Khatiwada et al [17].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mean insulin and HOMA-IR index in our patients with metabolic syndrome were 20.8±4.3 mU/mL and 5.8±1.3, respectively. Almost similar levels of mean insulin and HOMA-IR index were reported by Aldhafiri et al in patients with metabolic syndrome [16]. Compared to the findings of the current study, almost similar levels of FBS, serum TG, and HDL were reported by Khatiwada et al [17].…”
Section: Discussionsupporting
confidence: 88%
“…Meher et al reported similar outcomes [ 15 ]. A similar research was conducted by Aldhafiri et al, and the results showed that the mean systolic blood pressure and diastolic blood pressure were 130.44±2.82 and 88.17± 2.82 mmHg, respectively [ 16 ]. In the present study, we observed an elevated blood pressure in patients with metabolic syndrome as compared to patients without metabolic syndrome and a strong positive correlation of both systolic and diastolic blood pressure with TSH levels and a negative correlation with T3 levels.…”
Section: Discussionmentioning
confidence: 71%